An enhanced Total Lagrangian SPH for non-linear and finite strain elastic structural dynamics - Antonio Gil (Computational Mechanics, 2025)
The paper presents a variationally consistent Total Lagrangian SPH (TLSPH) model for non-linear and finite strain elastic structural dynamics. To enhance the approximation of stresses (dynamics) and thus accelerations (kinematics), the deformation gradient computation is enhanced to ensure second-order completeness and accordingly the discretized momentum equation is also reformulated so that the accelerations are consistently obtained with respect to the targeted second-order completeness. In addition, a novel Riemann stabilization term is proposed with respect to the rank deficiency of TLSPH particularly for challenging structural dynamics problems including fast dynamics and kinematical discontinuities. The new Riemann term is second-order accurate in space and includes a limiter for effective stabilization. This stabilization term is derived from the material acoustic tensor of the solid model employed, carefully accounting for both volumetric (compression) and shear wave contributions. The proposed TLSPH including the C2nd (2nd-order Completeness) and cR (complete Riemann term including volumetric and shear wave contributions) schemes is verified by considering six classical benchmark tests.